Mass media exposure and lassa fever risk perception in rural communities of South-south Nigeria - Erubami, Joshua Aghogho; Ojoboh, Lucky Ogheneruemu; Ohaja, Edith Ugochi; Ezugwu, Martins Ndubisi; Akata, Ukamaka Cecilia (Penerbit Universiti Kebangsaan Malaysia, 2022)
Nigeria bears the highest burden of Lassa fever in Africa, accounting for about 60% of the 5,000 annual mortalities attributable to the haemorrhagic disease. In the absence of preventive vaccines, the mass media have been deployed as independent and complementary interventions against the spread of the infection. This study examines the influence of mass media exposure on Lassa fever risk perception and risk behaviours among residents of eight rural communities in South-south Nigeria. Anchored on the Health Belief Model and Social Influence Theory, the study used survey questionnaires to collect data from 384 respondents selected through multistage sampling. Findings show that media exposure is positively related to Lassa fever risk perception (β = .519, 95% CI: .432, .607), but negatively associated with risk behaviours towards the zoonotic disease (β = -.797, 95% CI: -.922, -.671). Nevertheless, media influence on respondents’ risk perception and risk behaviours tends to vary significantly along sex, geographical region and employment status. Given the endemic nature of Lassa fever in Nigeria, the study recommends the sustenance of public sensitisation efforts aimed at preventing the spread of the disease, especially in rural areas. It also advocates the need for relevant health authorities to enforce healthier public environmental practices and initiate mastomys eradication programmes to reduce the presence of rats in residential areas.